717. Antibiotic treatment of Shiga toxin-producing Escherichia coli related gastroenteritis and the risk of hemolytic uremic syndrome: a population based matched case-control study in Japan. (31st December 2020) - Myojin, Shota; Pak, Kyongsun; Sako, Mayumi; Kobayashi, Tohru; Takahashi, Takuri; Sunagawa, Tomimasa; Igarashi, Takashi; Miyairi, Isao
Abstract: Background: The role of therapeutic intervention, particularly antibiotics, for Shiga toxin-producing Escherichia coli (STEC) related infection is controversial. Methods: We performed a population based matched case-control study to assess the association between treatment (antibiotics, antidiarrheal agents and probiotics) for STEC related infections and HUS development. We identified all STEC HUS patients as cases and matched five non-HUS patients as controls using the data from the National Epidemiological Surveillance of Infectious Diseases (NESID) between January 1, 2017, and December 31, 2018. Further medical information was obtained by standardized questionnaires answered by physicians who registered each patient. We used multivariate conditional logistic regression model to evaluate the association between exposures (use of antibiotics, use of antidiarrheal agents, days between disease onset and fosfomycin administration [within two or three days]) and the development of HUS, by matched odds ratios (OR) and 95% confidence intervals (CI). Covariates we used were sex, age group, area code, presence of diarrhea and other factors. We also performed subgroup analyses using age (adults and children) as a stratification factor. Results: 7, 760 STEC related patients were registered in the NESID. We selected patients who had a record of HUS diagnosis (n=182) and matched controls without HUS (n=910). After collecting standardized paper-based questionnaires, we enrolled 90 HUS patients and 371 non-HUS patients for analysis. In the main analysis, matched OR of fosfomycin was 0.75(0.47-1.20) in all ages, 1.41(0.51-3.88) in adults and 0.58(0.34-1.01) in children. Matched OR of antidiarrheal agents was 2.07(1.07-4.03) in all ages, 1.84(0.32-10.53) in adults, 2.65(1.21-5.82) in children. Matched OR of probiotics was 0.86(0.46-1.61) in all ages, 0.76(0.21-2.71) in adults, 1.00(0.48-2.09) in children. There was no significant association between the timing of fosfomycin use in the first two or five days of illness and HUS development in any age group. Conclusion: Our results suggest that fosfomycin might decrease the risk of HUS in children younger than 15 years of age with STEC confirmed bacterial gastroenteritis. Disclosures: All Authors : No reported disclosures